Gays, Lesbians and Bisexuals United [flier] - Cal Poly Gays, Lesbians and Bisexuals United::::::::: (1992)
Gays, Lesbians & Bisexuals United flier for their weekly meetings, held every Tuesday at 7:00 pm in Faculty Office Bldg (#47). The flier states: 'Confidentiality respected.'